2021
DOI: 10.3390/rs13245053
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Gully Erosion and Its Response to Human Intervention in the Tableland Region of the Chinese Loess Plateau

Abstract: The gully erosion process is influenced by both natural conditions and human activities on the tableland region, the Chinese Loess Plateau, which is a densely populated agricultural area with unique topography. For the purpose of assessing long-term gully growth rates, the influencing factors and potential of gully growth, KH-4B satellite images, Quickbird-2 images, and unmanned aerial vehicle (UAV) images were used to assess gully erosion from 1969 to 2019. The effects of runoff, topography and human activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Guo et al [32] reported that the SDR, SHC, SOM and MWD of gully heads significantly related to root diameter, RLD and root surface area density in the gullied region of the Loess Plateau. Furthermore, we found that some studies considered several soil properties including SHC, SDR, MWD, clay ratio, soil cohesion, and soil penetration resistance as indicators of soil erosion resistance [23,27,29,31,39,[50][51][52]. Therefore, the positive effects of vegetation roots on soil properties of gully heads fully manifested that the soil resistance of gully heads to erosion was closely affected by root distribution.…”
Section: Root Distribution and Soil Properties Of Gully Headsmentioning
confidence: 95%
See 4 more Smart Citations
“…Guo et al [32] reported that the SDR, SHC, SOM and MWD of gully heads significantly related to root diameter, RLD and root surface area density in the gullied region of the Loess Plateau. Furthermore, we found that some studies considered several soil properties including SHC, SDR, MWD, clay ratio, soil cohesion, and soil penetration resistance as indicators of soil erosion resistance [23,27,29,31,39,[50][51][52]. Therefore, the positive effects of vegetation roots on soil properties of gully heads fully manifested that the soil resistance of gully heads to erosion was closely affected by root distribution.…”
Section: Root Distribution and Soil Properties Of Gully Headsmentioning
confidence: 95%
“…For example, Frankl et al [56] found that the linear, areal, and volumetric retreat rate were 0.34 m yr −1 , 1.70 m 2 yr −1 and 5.20 m 3 yr −1 over the rainy reason of 2010, respectively, while larger rates were found during medium to long time periods (1-47 years), with averages of 3.8 m yr −1 , 31.5 m 2 yr −1 and 47.7 m 3 yr −1 in northern Ethiopia, respectively. Wang et al [23] reported the lower linear and areal retreat rate of 0.30 m yr −1 and 5.66 m 2 yr −1 from 1969 to 2010 in the tableland region of the Chinese Loess Plateau. The above comparison indicated that the gully headcut migration rate in the Mollisols area of northeast China is relatively higher than that in other areas of the world.…”
Section: Gully Headcut Migration and Its Response To Influencing Factorsmentioning
confidence: 99%
See 3 more Smart Citations